PRIMARY DYSMENORRHEA IN SCHOOL GOING ADOLESCENT GIRLS—IS IT RELATED TO DEFICIENCY OF ANTIOXIDANT IN DIET? Life Sciences-Physiology - PURUSHOTTAM PRAMANIK; SUBHA BOSE BANERJEE; PAYAL SAHA (International Journal of Life Science and Pharma Research, 2022)
Primary dysmenorrhea is the pelvic pain around the time of menstruation in the absence of pathological findings in adolescent girls. Increased oxidative stress is considered as one of the contributing factor in the pathogenesis of primary dysmenorrhea. The present study was to investigate the dietary intake status of antioxidants and primary dysmenorrhea. The present study was conducted among normal, healthy school girls of 12-17 years who attained menarche at least one year. 267 subjects of dysmenorrhea and 112 matched controls were included in this study. Weight and height were measured and dietary intake data were gathered by one day 24 hour recall method using an interview scheduled. The nutrient intake was assessed and compared with the recommended dietary allowances for the respective age group. The dietary antioxidant intake by each subject was computed in terms of Nutrient Adequacy Ratio (NAR). The subjects were categorized as those having an adequate (> 1.00), fairly adequate (0.66 to < 1.00) or inadequate (< 0.66) NAR for various nutrients. Average daily intake of beta carotene, vitamin-E and zinc was significantly higher in girls without dysmenorrhea than dysmenorrhagic counterpart. NAR for all antioxidants was higher for the control group than the experimental group of adolescent girls. Difference was significant for all study antioxidants except vitamin-C. Thus deficiency of antioxidant vitamins (particularly vitamin-E and beta carotene) and mineral, zinc may be a contributing factor of primary dysmenorrhea. Finally, it may be suggested that the dietary intake of antioxidants should be adequate for adolescent girls to minimize primary dysmenorrhea.